PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK STAD (STUDENT TEAM ACHIEVMENT DIVISIONS) UNTUK MENINGKATKAN LONG FOREHAND SERVICE PERMAINAN BULU TANGKIS - Maulana, Pajar; Suherman, Ayi; Rukmana, Anin (JURNAL ILMU KEOLAHRAGAAN, 2024)
This research aims to improve forehand serviceability using the STAD Student Team Achievement Division cooperative model). This research uses a quantitative approach with a pre-experimental design. The sample involved in this research is all students at SDN Babakan Bandung who take part in badminton extracurriculars. The research sample selection technique used was a total sampling of 18 people. Total sampling means the number of samples is the same as the population. The data collection technique used in this research is a test. The test carried out was a performance test of Nurhasan's long forehand service badminton ability. The data analysis test used the t-test with results showing a value of 0.01 < 0.05, which shows that the STAD learning model can improve long forehand serve ability in badminton. The normality statistical test uses Kolmogorov Smirnov with normal distribution results. Data from the t-test results with results of 0.001 < 0.05. So, there is a significant influence. The results of this test shown in R Square are 0.660, which means that the STAD learning model has a large influence of 66% on the long serve forehand in badminton.